EXPANDING THE USE OF INFORMATION TECHNOLOGY IN CASH FUNDS AUDIT - Kurbonov Farrukh, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In this article, the issues of using information technologies in the audit of cash funds are covered. The possibilities of improving the use of information technologies in the audit of cash funds are shown.